2018
DOI: 10.2478/ata-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Movement of the Wide Span Tractor-Based Field Machine Unit with Power Method of its Control

Abstract: Recently, rapid development of controlled traffic farming convincingly demonstrates the broad prospects of using the wide span tractor-based field machines throughout the world. The issue at hand lies in the fact that having a wide span tractor-based machine with steering-wheel system moving along the tracks of a constant technological track is not a rational option. According to the concept of bridge and rutting agriculture, it is advisable to subordinate the automated means of mechanization to the principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Given the general structure of the chassis and the steering mechanism of axle-driven machines, it has been scientifically proven that the simplest option is the on-board (power-driven) steering. These machines have motor wheels on two non-steerable axles and turn horizontally by varying the rotation speed of the front and rear wheels on the right and left side of the machine [12]. Despite the variety of specialised technical equipment, a curved movement (turning) takes place in the technological cycle of a wide span vehicle [13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the general structure of the chassis and the steering mechanism of axle-driven machines, it has been scientifically proven that the simplest option is the on-board (power-driven) steering. These machines have motor wheels on two non-steerable axles and turn horizontally by varying the rotation speed of the front and rear wheels on the right and left side of the machine [12]. Despite the variety of specialised technical equipment, a curved movement (turning) takes place in the technological cycle of a wide span vehicle [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These machines have motor wheels on two non-steerable axles and turn horizontally by varying the rotation speed of the front and rear wheels on the right and left side of the machine [12]. Despite the variety of specialised technical equipment, a curved movement (turning) takes place in the technological cycle of a wide span vehicle [13][14]. The peculiarity of operating wide span machines is that during operation they can make not only active (controlled) turns, but also passive ones, making a curvilinear movement not under the controlling influence of the operator, but under the influence of external forces [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that an increase in stress levels with higher bulk density and mechanical penetration resistance, and a decrease in soil hydraulic conductivity resulted in decreased root elongation rates and consequently prolonged the time required for roots to reach a certain soil depth. Soil compaction caused by machinery traffic needs to be: (a) either removed by costly subsoiling; or (b) avoided by implementation of technologies, such as wide span gantry technologies (Chamen, 2015;Bulgakov et al, 2018). Recently, controlled traffic farming (CTF) and its modifications show potential benefits worldwide (Godwin et al, 2015;Chamen, 2015;Gutu et al, 2015;Galambošová et al, 2017;Latsch and Anken, 2019;Antille et al, 2019;Masola et al, 2020).…”
mentioning
confidence: 99%
“…In order to investigate the dynamics of multi-element machines, the D'Alembert-Lagrange principle (Bulgakov et al, 2016) or the Lagrange equations of the 2 nd kind can be applied. Usually, research of the mobile machine movement is studied together with a semi-trailer by means of the Lagrange equations of the 2 nd kind (Chieh, 1995;Siew et al, 2009;Bulgakov et al, 2018). A mathematical model of the single machine movement has been repeatedly investigated (Blundell and Harty, 2004;Karkee and Seward, 2010).…”
mentioning
confidence: 99%